Aditus ad antrum patency on CT as a predictor of tympanoplasty outcomes in chronic otitis media - Ren, Yuan; Zhu, Xiaohui; Zhang, Lu; Kang, Cheng; Wang, Kai (Scientific reports, 2025)
To evaluate the prognostic significance of aditus ad antrum patency, as determined by computed tomography (CT), on the surgical outcomes in patients with chronic suppurative otitis media (CSOM). This study analyzed CSOM patients who had tympanoplasty at a tertiary hospital from 2015 to 2019. Patient demographics, operative reports, preoperative CT scans and outcomes were reviewed. Aditus ad antrum patency was evaluated on CT images. Outcome measures included graft success and postoperative air-bone gap (ABG) at the last follow-up (≥ 6 months). During the study, 138 patients with CSOM patients were included. Computed tomography (CT) scans revealed a blocked aditus in 37 patients (26.8%). Patients in the patent aditus group demonstrated a significantly better hearing prognosis compared to those in the obstructed aditus group ( P = 0.002). In the low- and intermediate-risk subgroups, patients with a blocked aditus exhibited significantly poorer postoperative hearing outcomes compared to those with a patent aditus ( P < 0.001). Multivariate logistic regression analysis identified obstructed aditus ad antrum (OR 1.83, 95% CI 1.10–3.04; P = 0.020) and a Middle Ear Risk Index (MERI) score greater than 3 (OR 2.68, 95% CI 1.06–6.75; P = 0.037) as independent adverse prognostic factors for hearing success in patients with CSOM. A patent aditus ad antrum correlates with preoperative dry ear, no middle ear granulation, a well-pneumatized mastoid, and a low MERI score. Preoperative CT showing aditus ad antrum patency may independently predict hearing outcomes and help stratify risk in CSOM patients.